2011
DOI: 10.1152/jn.00305.2011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional differences in voltage-activated sodium currents between GABA projection neurons and dopamine neurons in the substantia nigra

Abstract: Ding S, Wei W, Zhou FM. Molecular and functional differences in voltage-activated sodium currents between GABA projection neurons and dopamine neurons in the substantia nigra. J Neurophysiol 106: 3019-3034, 2011. First published August 31, 2011 doi:10.1152/jn.00305.2011 in the substantia nigra pars reticulata (SNr) and dopamine projection neurons (DA neurons) in substantia nigra pars compacta (SNc) have strikingly different firing properties. SNc DA neurons fire low-frequency, long-duration spikes, whereas SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 75 publications
4
56
0
Order By: Relevance
“…During steps to depolarized membrane potentials (Ͼ Ϫ30 mV), we hypothesize that a second slow component of sodium channel inactivation is present but cannot be observed because it is occluded by the faster entry into the fast inactivated state, and therefore inactivation has a monoexponential onset. During recovery from inactivation, however, a biexponential recovery is evident, which indicates that inactivation has a fast and a slow component (Ding et al 2011;Seutin and Engel 2010). Although variable fractions of the channels recorded in nucleated patches in these studies were reported to exhibit slow inactivation, in our model all channels exhibit slow inactivation.…”
Section: Methodsmentioning
confidence: 59%
See 2 more Smart Citations
“…During steps to depolarized membrane potentials (Ͼ Ϫ30 mV), we hypothesize that a second slow component of sodium channel inactivation is present but cannot be observed because it is occluded by the faster entry into the fast inactivated state, and therefore inactivation has a monoexponential onset. During recovery from inactivation, however, a biexponential recovery is evident, which indicates that inactivation has a fast and a slow component (Ding et al 2011;Seutin and Engel 2010). Although variable fractions of the channels recorded in nucleated patches in these studies were reported to exhibit slow inactivation, in our model all channels exhibit slow inactivation.…”
Section: Methodsmentioning
confidence: 59%
“…Previous models (Drion et al 2011;Kuznetsova et al 2010;Oster and Gutkin 2011) do not capture critical aspects of the firing rate limitation and how it is circumvented. Therefore we examined depolarization block in a simple model that faithfully reproduces the sodium current measured in these neurons (Seutin and Engel 2010) and also in a model with an additional slow component of sodium channel inactivation, recently observed in these neurons (Ding et al 2011). We discovered that these models entered into depolarization block in two different ways and experimentally demonstrated that a dopamine neuron can enter into depolarization block either way, depending upon the experimental conditions.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The main neuron type in the SNr is the GABA projection neurons that fire spontaneously around 10 Hz under in vitro conditions (Atherton and Bevan 2005;Ding et al 2011aDing et al , 2011b; Zhou and Lee 2011). The SNr also contains sparse dopamine neurons that fire spontaneously around 1.5 Hz under similar in vitro conditions (Connelly et al 2010;Ding et al 2011aDing et al , 2011bZhou et al 2006).…”
Section: Independent Elicitation Of Striatonigral and Pallidonigral Imentioning
confidence: 99%
“…The SNr also contains sparse dopamine neurons that fire spontaneously around 1.5 Hz under similar in vitro conditions (Connelly et al 2010;Ding et al 2011aDing et al , 2011bZhou et al 2006). Therefore, we first briefly recorded action potentials of neurons in SNr in a cell-attached mode in our angular sagittal brain slices (Fig.…”
Section: Independent Elicitation Of Striatonigral and Pallidonigral Imentioning
confidence: 99%